Dead shot : a sniper novel - Coughlin, Jack, 1966-; Davis, Don, 1939- (New York, NY : St. Martin's Press, 2009)
Kyle Swanson was once sniper in the Marine Corps, and is now a member of a special operations team known as Task Force Trident. Juba, a twisted mastermind and sniper, who is determined to seize control of the terrorist world from Al Qaeda, tests a new, devastating chemical weapon developed by Islamic terrorists at a British royal wedding in London, killing hundreds of people. It's Swanson's mission to hunt down Juba.
Includes excerpt from the authors' book, Clean kill: a sniper novel (p.[335]-345).
Keywords: Terrorists -- Fiction; Snipers -- Fiction; Undercover operations -- Fiction; Suspense fiction